The internal governance model in Chinese universities: an international comparative analysis. (1st July 2019) - Liu, Wei; Yan, Weigang
Abstract : Purpose: The purpose of this paper is to glean a comprehensive picture of the internal governance structure in Chinese universities based on data from 40 university administrators from 33 Chinese institutions. Design/methodology/approach: The 40 administrators were convenience sampled while they were taking a three-month higher education leadership development program in a large public university in Canada. Permission was obtained to use the comparative discussions at different reflective research sessions as data to inform this study. The data were also progressively collected through informal interviews throughout the three months. Findings: The study finds that the current governance model practiced in Chinese universities can be called "administrator governance, " with all members on the two major governing bodies being senior administrators appointed by and accountable for the governments. To build a "modern university system" aspired in China, the Chinese university administrators perceived a need to strengthen institutional autonomy and collegial governance with participation of the faculty and students. Originality/value: As much of the literature has focused on the government–university relationship in China, this study aims to glean a comprehensive picture of the internal governance structure in Chinese universities.